Brazil : Interoperability of ATMs - World Bank (World Bank, Washington, DC, 2020)
The joint World Bank - International Monetary Fund (IMF) financial sector assessment program (FSAP) of 2018 recommended for the Banco Central do Brasil (BCB) to pursue full interoperability of automated teller machine (ATM) networks in Brazil. Following the FSAP and the policy dialogue with BCB, this note aims to provide key policy options for BCB with respect to achieving interoperability for ATM transactions in Brazil. The note presents: (i) the key concepts that impact interoperability of the ATM network; (ii) an overview of the regulatory framework and retail payment infrastructure in Brazil; (iii) cross country examples of interoperable ATM networks; (iv) issues and challenges to be addressed for achieving interoperability; and (v) the possible policy options that the BCB can consider adopting in Brazil. It elaborates policy options with regards to: (i) interoperability of the ATM network - the feasibility of enforcing interoperability among all financial institutions, (ii) relevance of having an independent authorized ATM network, and (iii) whether to leave the pricing of ATM services to the market or should BCB consider regulating the same.